The Revision of the Crustacea Collection of the Museum of Zoology “P. Doderlein” under the Framework of the National Biodiversity Future Center - Pipitone, Carlo; Innocenti, Gianna; Pepe, Paola; Tumbiolo, Maria; Lo Brutto, Sabrina (Diversity (Basel), 2023)
The collection of Crustacea preserved in the Museum of Zoology “P. Doderlein” in Palermo (Italy) has been revised in the framework of the activities of the National Biodiversity Future Center. The main part of the collection is composed of Decapoda, while a smaller part includes Stomatopoda, Isopoda, Amphipoda, and Cirripedia. Overall the collection includes common species, some of which are now protected.